Efektivitas Monitoring Harga Minyakita dalam Menghadapi Kendala Praktik Bundling Agen di Pasar Karah Surabaya - Dalfon Refaim Aruan; Nurjanti Takarini (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Despite government intervention through price control measures, price instability of necessities continues to be a persistent problem in local markets. This study looks at how well Surabaya City's Department of Cooperatives, Small and Medium Enterprises, and Trade (Dinkopdag) monitors prices in response to Minyakita pricing discrepancies brought on by bundling practices at Karah Market. The study intends to examine how price control is implemented, pinpoint distribution obstacles, and elucidate the causes of price increases that surpass the Highest Retail Price (HET). Participatory observation and in-depth interviews with two officially designated monitoring dealers were conducted between October and December 2025 as part of a qualitative case study methodology. The results show that dealers' reliance on intermediate agencies enforcing mandated bundling sales caused Minyakita prices to rise from Rp 17,000 to Rp 18,000 per liter, above the HET of Rp 15,700 per liter. The suggested direct distribution technique has not yet evenly reached micro-traders, despite Dinkopdag's active price monitoring and identification of the problem. This study emphasizes that in order to avoid market distortion and safeguard small merchants, fair access to official distribution channels is necessary for efficient pricing monitoring.